A Z-linked sterility locus causes sexual abstinence in hybrid females and facilitates speciation in Spodoptera frugiperda - Kost, Silvia; Heckel, David G; Yoshido, Atsuo; Marec, František; Groot, Astrid T (Evolution; international journal of organic evolution, 2016)
In the fall armyworm, Spodoptera frugiperda (Lepidoptera, Noctuidae), two sympatric strains have been recognized that have been termed corn strain (C) and rice strain (R), referring to their most common host plants. Both strains are reproductively isolated via a distinct prezygotic barrier as well as via an intriguing postzygotic phenomenon: when R females have mated with C males, the resulting RC hybrid females exhibit dramatically reduced fertility independent of their mating partner. Here, we demonstrate that the reduced fertility is caused by the fact that these females refrain from mating, that is, females are behaviorally sterile. We identified a Z-chromosomally linked sterility locus that is most likely incompatible with yet to be identified autosomal (or cytoplasmic) factors, leading to the observed sexual abstinence. Within-chromosome mapping revealed the sterility locus to be located in an area of strongly reduced interstrain recombination.
Keywords: reprodukční izolace; Spodoptera; sex chromosome; Genetic Linkage; sexuální chování zvířat; sex chromosomal-autosomal incompatibility; United States; genetická vazba; fenotyp; hybrid incompatibility; Phenotype; Reproductive Isolation; zvířata; mapování chromozomů; Spojené státy americké; Chromosome Mapping; Hybridization, Genetic; hybridizace genetická; Behavioral sterility; Sexual Behavior, Animal; unidirectional sterility; Animals